Effects of Remote Physiotherapy on Neck Pain, Functionality, Fatigue and Sleep Quality in Violinist - Gabrielė Tverkutė; Ligita Šilinė (Lithuanian Sports University, 2022)
Background. Due to the high physical and psychological demands of their work, musicians face a variety of musculoskeletal disorders that negatively affect both quality of life and musical performance. The main risk factor for these disorders is poor posture of the violinist. Targeted physiotherapy reduces muscle imbalance and pain, thus improving posture and quality of life. Studies have shown that remote physiotherapy may be effective in musculoskeletal disorders but is not commonly used. Thus, the effects of remote physiotherapy on neck pain, functional status, fatigue, and sleep quality in violinist are still unclear. Aim. To determine the effect of remote physiotherapy on neck pain, functional status, fatigue, and sleep quality in violinist. Methods. The study included 9 women professional violinists. Physiotherapy was applied for 6 weeks, 4 days a week. Pre and post intervention, the subjects were assessed for pain using the visual analogue scale, and the neck disability index, for sleep quality with the Pittsburgh sleep quality index, and for fatigue with the fatigue index. Results. There was a reduction in pain (p <0.001), physical fatigue (p = 0.004) and functional impairment (p = 0.013) after applying physiotherapy. Activity increased (p = 0.016) and sleep quality improved (p = 0.002) after intervention. Conclusion. Remotely-used physiotherapy reduced the pain and fatigue felt by professional violinists and improved functional status and sleep quality. Keywords: posture, telerehabilitation, quality of life, musicians